Robust stability analysis and controller synthesis for uncertain impulsive positive systems under L1-gain performance. (October 2019) - Zhu, Baolong; Zhang, Jie; Suo, Mingliang; Chen, Liangming; Zhang, Yanquan; Li, Shunli
Abstract: This paper addresses the problems of robust stability analysis and L 1 -gain controller synthesis for uncertain impulsive positive systems. First, by employing the idea of impulse interval partitioning, an impulse-time-dependent discretized copositive Lyapunov function is proposed to analyze the robust stability and L 1 -gain performance of the considered system without control inputs, and several stability conditions and L 1 -gain criteria are respectively derived. Subsequently, a sufficient condition is formulated for the existence of state-feedback controllers with which not only the positivity and robust uniform asymptotic stability of the resulting closed-loop system are guaranteed, but also a prescribed L 1 -gain performance is satisfied simultaneously. Furthermore, to make the controller synthesis problem numerically tractable, we propose an iterative convex optimization algorithm to compute the desired controller parameters. Finally, three numerical examples and two realistic examples are presented to show the effectiveness and applicability of the proposed methodology. Highlights: Several sufficient conditions about the RUAS and L 1 -gain performance are developed. A sufficient condition for the existence of the L 1 -gain controller is derived. An iterative convex algorithm is developed to compute the controller parameters.